ANALYSIS OF GRAMMATICAL INTERFERENCES IN THE ORAL COMMUNICATION PRESENTED BY PIBBI PARTICIPANTS - Ekawati, Priscilla Agna (Universitas Pendidikan Indonesia, 2018)
This present study aims to analyse and describe features of L1 interference in oral communication by PIBBI Participants of Level 5 who enrolled in an intensive language program at LTC, SWCU. The data were collected by giving oral tasks when describing something, giving opinion and explaining how things work. A stimulated recall interview proposed by Dornyei (2007) was used to explore the findings in detail. The analysis presents the type of grammatical interferences, the frequency of occurrence of each interference type and their detailed description. Analysis of data revealed that students in high level still experience grammatical interferences in producing Indonesian speech. It is hoped that this study will give a better suggestion for the advanced foreign language learners and provide information for teachers on common interferences in language learning which can be used as a reference in developing the teaching materials.Â